STRENGTHENING CHARACTER EDUCATION THROUGH SCOUTING AND EXTRACURRICULAR ACTIVITIES - Ahmad Jarnawi Lubis; Jamaluddin; Hamka (PT. Jurnal Center Indonesia Publisher, 2026)
Character education is a crucial aspect in shaping students' personalities to be faithful, virtuous, independent, and responsible. One effective strategy for strengthening character education is through scouting and extracurricular activities implemented in schools. This study aims to describe the role of scouting and extracurricular activities in strengthening students' character values and to identify their implementation and impact on students' attitudes and behavior. The research method used was a qualitative approach, with data collection techniques through observation, interviews, and documentation. The results indicate that scouting and extracurricular activities are able to instill the values of discipline, cooperation, leadership, responsibility, independence, and social awareness in a contextual and sustainable manner. The process of habituation, the role model of the instructor, and direct experience in the activities are key factors in the success of strengthening students' character. Therefore, scouting and extracurricular activities have a strategic contribution in supporting character education strengthening programs in schools and need to be managed systematically and integrated with learning activities.